Methodological Possibilities of the Theo-aesthetics for the Analysis of Cultural Artifacts - Denys KONDYUK (Богословські роздуми: Східноєвропейський журнал богословʼя)
This study presents a certain perspective on viewing reality through the lens of theological aesthetics. In particular through the concept of Beauty as a transcendental as presented by David Bentley Hart. Thus, his treatment of the concept by Gregory of Nyssa is applied to the analysis of cultural artifacts. So, the study concentrates on the concepts of epektasis, apatheia, and perichoresis as presented by Hart. There is also a short overview of analogia entis in relation to discovering God's revelation in different art pieces. On a practical level this study bases this discovery on an example of film analysis, which could be used as a methodological matrix for the analysis of other cultural artifacts.